The Oligomerization of Phosphinoborane by Titanium Complexes. Issue 19 (10th April 2013) - Thoms, Christine; Marquardt, Christian; Timoshkin, Alexey Y.; Bodensteiner, Michael; Scheer, Manfred
Abstract : The PB chain gang : The reactions of an acetylene complex of titanocene with the parent phosphinoborane stabilized only by a Lewis base lead to novel phosphinoborane oligomers coordinated by Cp2 Ti complex fragments. Depending on the reaction conditions (temperature and stoichiometry), unprecedented oligomeric chains of phosphinoborane are obtained by dehydro‐oligomerization and PP coupling reactions. btmsa = bis(trimethylsilyl)acetylene.